Winter wheat variability according to local conditions - Mykola NAZARENKO; Irina SOLOHUB; Olexandr IZHBOLDIN (Acta Agriculturae Slovenica)
The objectives of our experiments are the description of the phenotypic and genotypic variability by the main agriculture-value traits of the new winter wheat lines according to their interactions with different environmental conditions. Five new winter wheat lines were investigated at field experiment during three years by parameters of grain productivity and quality, uptaking of macro- and microelements and heavy metals from soil under different relief conditions.